Estudo da composição química e da atividade antimicrobiana in vitro dos óleos essenciais de espécies do gênero Myrcia DC. (Myrtaceae) - Silva, Aline do Nascimento (2010)
The family Myrtaceae comprise more than 3.100 species, wich are widely distributed in America and Australia. The genus Myrcia DC., include 300 species in all Brazilian territory and approximate 52 species reside in Bahia state. This work reports the seasonal variation of the composition of leaf essential oils of Myrcia alagoensis O. Berg, Myrcia guianensis (Aubl.) DC. and Myrcia rostrata DC. harvested in the remainder of forest in the municipal district of Alagoinhas, Bahia, northeastern region of Brazil in four different season during the years 2008 and 2009. The essential oils were obtained by hydro-distillation from fresh leaves after three hours in a Clevenger apparatus. The oils were analyzed by GC-FID and GC-MS. Different compounds were identified with predominancy of the sesquiterpenes, for example Carotol, β- Farnesene (E), Caryophyllene, Germacrene D and Methyl Farnesoate (2E, 6E), which were predominant in most of the analyzed samples. The chemical composition from all essential oil samples showed meaningful seasonal variation. All the sample oils, with exception of Myrcia guianensis (Aubl.) DC., had their antimicrobial properties tested against seven bacteria (Staphylococcus aureus resistant a novobiocine, Staphylococcus aureus resistant a streptomycin and dihidrostreptomycin, Bacillus cereus, Escherichia coli, Escherichia coli sensitive a trimetoprime and resistant a sulphonamide, Salmonella choleraesuis and Pseudomonas aeruginosa) and two yeasts (Candida albicans and Candida parapsilosis) by the broth microdilution method. The Minimal Inhibitory Concentration (MIC) was determinate and the essential oils were active against all microorganisms evaluated.